Mathematics anxiety and associated interventions in nursing: A scoping review. (May 2022) - McKenna, Lisa; Johnston, Jacqueline; Cross, Rachel; Austerberry, Jen; Mathew, Thomas; McKenzie, Gayle
Abstract: Background: Mathematics proficiency is a key element in accurate medication calculation and patient safety. Education providers play an important role in preparing students for safe medication administration. However, the presence of mathematics anxiety in students may impact on relevant mathematics mastery. Objectives: To explore what is known and reported about mathematics anxiety in nursing and the nature of interventions developed. Design: A scoping review guided by the work of Arksey and O'Malley and Joanna Briggs Institute methodology. Data sources: CINAHL, Medline, ERIC and Proquest Nursing and Allied Health. Review methods: Search included primary research published between 2000 and 2021 and in English language. Results: Ten studies were included in the final review, and numerous different tools used to measure mathematics anxiety. A number of factors were found to influence mathematics anxiety and various local interventions are reported. There is a lack of consistency in research reporting on mathematics anxiety, with most being single-site studies and small in scale. Conclusions: Overall, despite its importance, there is scant research into mathematics anxiety in nursing. There is a need for a consistent, valid and reliable tool for its measurement, as well as validated interventions to address it. Furthermore, there is a deficit in research evaluating mathematics anxiety longitudinally across the duration of an education program. There is a need for nurse education providers to work to address these important gaps and establish entry-level benchmark requirements. Highlights: Proficiency with mathematics is a key contributor to patient safety. There is limited research exploring mathematics anxiety in nursing students. There is a need for longitudinal research on progression of mathematics anxiety.